2015
DOI: 10.1002/marc.201500076
|View full text |Cite
|
Sign up to set email alerts
|

Dual Enzyme‐Responsive Capsules of Hyaluronic Acid‐block‐Poly(Lactic Acid) for Sensing Bacterial Enzymes

Abstract: The synthesis of novel amphiphilic hyaluronic acid (HYA) and poly(lactic acid) (PLA) block copolymers is reported as the key element of a strategy to detect the presence of pathogenic bacterial enzymes. In addition to the formation of defined HYA-block-PLA assemblies, the encapsulation of fluorescent reporter dyes and the selective enzymatic degradation of the capsules by hyaluronidase and proteinase K are studied. The synthesis of the dual enzyme-responsive HYA-b-PLA is carried out by copper-catalyzed Huisgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 31 publications
4
47
0
Order By: Relevance
“…15,16,17,18 In different strategies, virulence factors secreted by pathogenic bacteria are targeted for the in situ detection. 19,20,21,22 Zakir Hossain et al 23 reported for instance on a lab-onpaper assay for the rapid and sensitive detection of E. coli in water. In this method the reporter 5 elements were printed on a small paper strip.…”
Section: Introductionmentioning
confidence: 98%
“…15,16,17,18 In different strategies, virulence factors secreted by pathogenic bacteria are targeted for the in situ detection. 19,20,21,22 Zakir Hossain et al 23 reported for instance on a lab-onpaper assay for the rapid and sensitive detection of E. coli in water. In this method the reporter 5 elements were printed on a small paper strip.…”
Section: Introductionmentioning
confidence: 98%
“…1, 2 Due to their mechanical stability, 1, 3, 4 capacity for additional functionalization, and lower permeability, 5 polymersomes offer significant advantages over other bilayer vesicle in encapsulating and transporting enzymes, 6, 7 proteins, 8, 9 drugs, 914 and biomedical imaging and diagnostics. 1518 Furthermore, the interior compartment of polymersomes has been engineered to serve as a micro-environment for protein expression, 8 gene expression, 19 and enzymatic reaction. 6, 7, 2023 Blending each of these functions into different compartments within polymersomes could potentially lead to the development of protocells that mimic the metabolism, 6 enzymatic activity, 6, 7, 2022, 24 and communications of real cells.…”
mentioning
confidence: 99%
“…Somatologically favorable enzymatic reactions also have been used to control the release of encapsulants from polymersomes. 14, 17, 18, 23 Although these strategies have successfully shown the disruption of polymersomes to trigger the release of encapsulants, few studies have demonstrated the ability to tailor the rate of rupture/release using an enzyme cascade which can be readily controlled by the concentration of substrate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various new formats for rapid, sensitive and selective bacteria detection, vesicle based approaches, autonomously reporting hydrogel films, as well as hydrogel dot microarrays have garnered particular attention. These formats mainly rely on the detection and reporting of secreted bacterial enzymes, DNA, and virulence factors . For many infections, such as wound infections, bacteria reside in a so‐called biofilm, which represents a confluent community of bacteria protected by an extracellular polymeric matrix .…”
Section: Introductionmentioning
confidence: 99%